On the mechanisms of prevention destruction of pancreatic B-cells induced by direct action of zinc binding chelators by reduced form of glutathione - Meyramov, G.G.; Shaуbek, A.S. (Fundamental and Experimental Biology, 2018)
It is known that reduced form of amino acid the glutathione (GRF), containing in structure of a molecule of SH-radical is capable to prevent developing of diabetes caused by group of diabetogenic zincbinding chemicals whereas the oxidized form of the glutathione (GOF) contrary to GRF only what does not contain in a molecule of SH-group, was completely incapable to prevent developing of diabetum caused by this group of substances. It was shown that treatment of animal GRF is followed by emergence the completely negative reaction to zinc B-cells that it is possible to explain withbinding of zinc with GRF what interfered with its interaction with diabetogenic ligands. The model of the isolated pancreatic islets at which the direct influence of substances on B-cells excluding possible interactions of the studied substances in blood and tissues is provided was applied to obtaining more convincing proofs. Results demonstrate that direct influence of GRF on B-cells of the isolated pancreatic islets really leads to binding zinc of B-cells thanks to what its interaction with diabetogenic helator is prevented. At the same time results demonstrate that preventive action of GRF contrary to GOF is caused by existence in structure of its molecule SH-group through which is forming a complex of zinc with GRF that protect destruction of B-cells at subsequent influence of diabetogenic zincbinding chemicals.